Endoplasmic reticulum retention motif fused to recombinant anti-cancer monoclonal antibody (mAb) CO17-1A affects mAb expression and plant stress response - Song, Ilchan (PLoS One, 2018)
The endoplasmic reticulum (ER) is the main site of protein synthesis, folding, and secretion to other organelles. The capacity of the ER to process proteins is limited, and excessive accumulation of unfolded and misfolded proteins can induce ER stress, which is associated with plant diseases. Here, a transgenic Arabidopsis system was established to express anti-cancer monoclonal antibodies (mAbs) that recognize the tumor-associated antigen GA733-2. Monoclonal antibody (mAb) CO17-1A recognize a tumor-associated epitope expressed on the colorectal cancer cell surface. The ER retention Lys-Asp-Glu-Leu (KDEL) motif sequence was added to the C-terminus of the heavy chain to retain anti-colorectal cancer mAbs in the ER, consequently boosting mAb production. Agrobacterium-mediated floral dip transformation was used to generate T(1) transformants, and homozygous T(4) seeds obtained from transgenic Arabidopsis plants expressing anti-colorectal cancer mAbs were used to confirm the physiological effects of KDEL tagging. Germination rates were not significantly different between both plants expressing mAb CO without KDEL mAb CO (CO plant) and mAb CO with KDEL mAb COK (COK plant). However, COK plants primary root lengths were shorter than those of CO plants and non-transgenic Arabidopsis plants in in vitro media. Most ER stress-related genes, with the exception of bZIP28 and IRE1a, were upregulated in COK plants compared to CO plants. Western blot and SDS-PAGE analyses showed that COK plants exhibited up to five times higher expression and mAb amounts than plants. Enhanced expression in mAb COK plants was confirmed by immunohistochemical analyses. mAb COK was distributed across most of the area of leaf tissues, whereas mAb CO was mainly distributed in extracellular areas. Surface plasmon resonance analyses revealed that mAb CO and mAb COK possessed equivalent or slightly better binding activities to antigen EpCAM compared to a commercially available parental antibody. N-glycosylation analysis showed that mAb CO had plant specific residues whereas mAb COK mainly showed an oligo-mannose N-glycan structure without the plant specific glycan residues. In this study, the reduction of plant growth and biomass induced by ER retention signal peptide might be only in in vitro conditions, and thus should be carefully considered for the initial screening for transgenic lines on culture media. Taken together, nevertheless the fusion of ER retention signal peptide is an effective approach for enhancing the yields of recombinant proteins in vivo.